Information Frictions and Adverse Selection: Policy Interventions in Health Insurance Markets - Handel, Benjamin R.; Kolstad, Jonathan T.; Spinnewijn, Johannes (The Review of Economics and Statistics, 2019)
Despite evidence that many consumers in health insurance markets are subject to information frictions, approaches used to evaluate these markets typically assume informed, active consumers. We develop a general framework to study insurance market equilibrium in the presence of choice frictions and evaluate key policy interventions. We identify sufficient relationships between the underlying distributions of consumer costs, surplus from risk protection, and choice frictions that determine the welfare impact of friction-reducing policies. We implement our approach empirically, showing how these key sufficient objects can be measured and the link between these objects and policy outcomes.